Katekese sebagai Sarana Pewartaan Iman di Era Digital: Studi Pemanfaatan Platform TikTok - Elisabeth Yecilda Woga; Monica Innanda Chiaralazzo; Intansakti Pius X (Sabar : Jurnal Pendidikan Agama Kristen dan Katolik, 2026)
Advances in digital technology have transformed the paradigm of faith proclamation, requiring the Church to optimize social media as a relevant catechetical instrument. This study aims to examine how the use of the TikTok platform can be optimized as an effective means of creative catechesis in connecting complex faith teachings for people in the digital era. The research method used is descriptive qualitative with a literature study technique, where data is collected from various scientific literature, Church documents, and relevant library sources. The research findings indicate that TikTok is an effective digital space for catechesis because it is supported by attractive audio-visual features, interactive features such as stitches and comments that enable two-way dialogue, and an algorithmic system that expands the reach of proclamation. The strategy of catechesis through short videos has proven to be able to change the perception of faith teaching that has become rigid to a more personal spiritual experience that is easily understood by all levels of society, especially the younger generation. The implications of this study emphasize the need for the Church to consistently adapt to digital culture and increase content creativity to ensure the continuity of inclusive evangelization amidst the dynamics of modern developments.